2018
DOI: 10.1155/2018/1435030
|View full text |Cite
|
Sign up to set email alerts
|

Neural Prosthetics:A Review of Empirical vs. Systems Engineering Strategies

Abstract: Implantable electrical interfaces with the nervous system were first enabled by cardiac pacemaker technology over 50 years ago and have since diverged into almost all of the physiological functions controlled by the nervous system. There have been a few major clinical and commercial successes, many contentious claims, and some outright failures. These tend to be reviewed within each clinical subspecialty, obscuring the many commonalities of neural control, biophysics, interface materials, electronic technologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 136 publications
0
30
0
Order By: Relevance
“…In the nervous system, pulsatile stimulation was in principle confined to evoking an action potential (AP) in response to a pulse. However, due to the gross spatiotemporal spike rate coding method of the peripheral nervous system, pulsatile stimulation offered such a broad realm of applications that IPG technology dominated the field of neuromodulation for many years and it is still the primary commercial technology for neuromodulation therapies (Loeb, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the nervous system, pulsatile stimulation was in principle confined to evoking an action potential (AP) in response to a pulse. However, due to the gross spatiotemporal spike rate coding method of the peripheral nervous system, pulsatile stimulation offered such a broad realm of applications that IPG technology dominated the field of neuromodulation for many years and it is still the primary commercial technology for neuromodulation therapies (Loeb, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…(Jayathilaka et al, 2019). Besides, the sensing masks would contribute an extended degree of freedom for health care assessment, by providing respiration diagnosis regarding the respiration rate and the exhaled gases (Su et al, 2020a;2018;2017;Wang et al, 2019e). Implanted bioelectronics, on the other hand, provides new feasibilities in detecting biological signals and stimulating nervous systems or organs (Lee and Lee, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Implanted bioelectronics, on the other hand, provides new feasibilities in detecting biological signals and stimulating nervous systems or organs ( Lee and Lee, 2018 ). Besides, neural prostheses can assist patients by enhancing their sensory, cognitive, and motor modalities ( Loeb, 2018 ; Wang et al., 2020a ). The eventual realization of the exhaustive bodyNET will provide insightful information for disease diagnosis, preventive health care, rehabilitation, and even prompt treatment with the aid of surging drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%
“…Most neural prostheses including vestibular prostheses rely on biphasic charge-balanced pulses to stimulate the neural tissue [15]. It has previously been shown that the application of anodal direct current (DC) to the vestibular system can inhibit baseline activity in the vestibular nerve [9].…”
Section: Introductionmentioning
confidence: 99%